Genome-Wide Divergence and Linkage Disequilibrium Analyses for Capsicum baccatum Revealed by Genome-Anchored Single Nucleotide Polymorphisms - Nimmakayala, Padma; Abburi, Venkata L.; Saminathan, Thangasamy; Almeida, Aldo; Davenport, Brittany; Davidson, Joshua; Reddy, C. V. Chandra Mohan; Hankins, Gerald; Ebert, Andreas; Choi, Doil; Stommel, John; Reddy, Umesh K. (Frontiers in Plant Science, 2016)
Principal component analysis (PCA) with 36,621 polymorphic genome-anchored single nucleotide polymorphisms (SNPs) identified collectively for Capsicum annuum and Capsicum baccatum was used to show the distribution of these 2 important incompatible cultivated pepper species. Estimated mean nucleotide diversity (π) and Tajima’s D across various chromosomes revealed biased distribution toward negative values on all chromosomes (except for chromosome 4) in cultivated C. baccatum, indicating a population bottleneck during domestication of C. baccatum. In contrast, C. annuum chromosomes showed positive π and Tajima’s D on all chromosomes except chromosome 8, which may be because of domestication at multiple sites contributing to wider genetic diversity. For C. baccatum, 13,129 SNPs were available, with minor allele frequency (MAF) ≥0.05; PCA of the SNPs revealed 283 C. baccatum accessions grouped into 3 distinct clusters, for strong population structure. The fixation index (FST) between domesticated C. annuum and C. baccatum was 0.78, which indicates genome-wide divergence. We conducted extensive linkage disequilibrium (LD) analysis of C. baccatum var. pendulum cultivars on all adjacent SNP pairs within a chromosome to identify regions of high and low LD interspersed with a genome-wide average LD block size of 99.1 kb. We characterized 1742 haplotypes containing 4420 SNPs (range 9–2 SNPs per haplotype). Genome-wide association study of peduncle length, a trait that differentiates wild and domesticated C. baccatum types, revealed 36 genome-wide SNPs significantly associated. Population structure, identity by state (IBS) and LD patterns across the genome will be of potential use for future genome-wide association study of economically important traits in C. baccatum peppers.